SFM Fetal Therapy Practice Guidelines: Fetal Tissue Biopsy - Sharma, Aparna K.; Rana, Anubhuti (Journal of Fetal Medicine, 2023)
Prenatal diagnostic invasive procedures are used to determine if a fetus is at risk of a genetic disease. Analysis based on cells obtained from amniocentesis or chorionic villous sampling is the more commonly performed prenatal diagnostic invasive procedure. For certain indications, however, fetal skin biopsy, muscle biopsy, kidney biopsy, and fetal tissue biopsy of a tumor or mediastinal mass have also been performed. These procedures are rarely indicated in the current scenario when molecular tests are available for most of the genetic conditions. However, there are some genetic conditions for which no specific molecular test is available and prenatal diagnosis can only be done by biopsy of the fetal part during ultrasound guidance.
Keywords: fetal skin biopsy; fetal tissue biopsy; fetus; ultrasound; prenatal